2023
DOI: 10.3389/fevo.2022.1031664
|View full text |Cite
|
Sign up to set email alerts
|

Initial herbivory and exposure to herbivory-induced volatiles enhance arthropod species richness by diversifying community assemblages

Abstract: Plant ecological traits affect the species identity of plant-colonizing arthropods, which in turn induces species-specific trait changes in plants, forming feedback between plants and arthropods. Such feedback can amplify initial differences in species composition, leading to large variations (i.e., high β diversity). We hypothesized that the differences in plant initial conditions have sustained effects on arthropod community composition and species richness. To test this hypothesis, we monitored arthropod co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 53 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…In conclusion, our study found that both PVOCs and priority effects played a significant role in the short-term, initial stages of community assembly of arthropods on willow trees. Although our monitoring was limited to the initial stages, we predict that the effects of community divergence observed in our study was not transient but could persist in a longer timescale, at least for several months, based on previous studies (Stam et al, 2018;Yoneya et al, 2023) indicating such lasting effects. Our study indicated that riparian willow forests are an excellent model system for community assembly, along with recent studies focusing on the local co-occurrence of multiple willow species (Yoneya et al, 2012), its temporally dynamic characteristics (Nakamura et al, 2005), plant volatile-mediated food chains (Yoneya & Takabayashi, 2013), and high diversity of arthropods (Nakamura et al, 2006;Yoneya et al, 2023).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In conclusion, our study found that both PVOCs and priority effects played a significant role in the short-term, initial stages of community assembly of arthropods on willow trees. Although our monitoring was limited to the initial stages, we predict that the effects of community divergence observed in our study was not transient but could persist in a longer timescale, at least for several months, based on previous studies (Stam et al, 2018;Yoneya et al, 2023) indicating such lasting effects. Our study indicated that riparian willow forests are an excellent model system for community assembly, along with recent studies focusing on the local co-occurrence of multiple willow species (Yoneya et al, 2012), its temporally dynamic characteristics (Nakamura et al, 2005), plant volatile-mediated food chains (Yoneya & Takabayashi, 2013), and high diversity of arthropods (Nakamura et al, 2006;Yoneya et al, 2023).…”
Section: Discussionmentioning
confidence: 53%
“…Our results suggest that both the priority effect and environmental filtering play significant roles in the observed community assembly processes. Linkage between the earliest and subsequent colonizer communities suggests the presence of priority effects caused by plant-arthropod feedback (Utsumi et al, 2010;Yoneya et al, 2023).…”
Section: Priority Effectmentioning
confidence: 99%
See 3 more Smart Citations